Upaya Peningkatan Perilaku Masyarakat Melalui Edukasi Pencegahan DBD di Kelurahan Legok Kota Jambi - Hidayat, Muhammad -; Hesty, Hesty; Indrawati, Iin; Maimaznah, Maimaznah; Sari, Mila Triana (Universitas Baiturrahim, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease that occurs at all ages with the main symptoms of fever, muscle and joint pain which usually worsen after the first 2 days. It is prevented through 3 factors of transmission of dengue infection, namely: humans, viruses, and intermediary factors but due to lack of knowledge of the RT 20 community regarding efforts to prevent dengue fever so that it has a negative impact on the RT 20 community. Efforts that can be made by the community service implementation team are providing health education to the community. The target and output of this community service activity is an effort to improve community behavior through dengue prevention education in Legok Village, Jambi City. Implementation methods are surveys, observations, interviews, discussions and demonstrations through health education. This activity was attended by 10 people from RT 20, This series of activities will be carried out in March-August 2023 in the homes of residents of the Legok sub-district, Jambi City. The results of this activity were that participants answered questions about preventing dengue fever correctly, participants applied the principles of preventing dengue fever, participants were able to organize dengue fever prevention activities to support the prevention of dengue fever. In conclusion, there is an increase in public knowledge about the importance of preventing dengue fever, residents of the Legok sub-district, Jambi City can know about preventing dengue fever in their respective home environments.